Characteristics of mass-forming autoimmune pancreatitis commonly misdiagnosed as a malignant tumor - Chen, Si; Zhang, Hanlei; Fang, Fang; Ye, Chao; Zhang, Kaiguang (Frontiers in Surgery, 2023)
This study aimed to explore the clinical characteristics and differential diagnosis of patients with autoimmune pancreatitis (AIP) and pancreatic cancer to prevent misdiagnosis and mistreatment. The clinical data of patients with AIP with suspected pancreatic or bile duct malignancy and pancreatic cancer were retrospectively analyzed. AIP was commonly observed in men. Compared to patients with pancreatic cancer, the incidence of poor appetite and weight loss and carbohydrate antigen 19-9 (CA19-9) level was lower in patients with AIP, while the immunoglobulin G4 (IgG4) level was higher (p<0.05). After treatment, the IgG4 and CA19-9 levels in patients with AIP were decreased (p<0.001). IgG4 level before treatment (OR=2.452, 95%CI: 1.180-5.096, P=0.016) and total bilirubin (Tbil) level before treatment (OR=0.992, 95%CI: 0.985-0.998, P=0.013) were independent risk factors of AIP. Furthermore, the diagnostic value of IgG4 level before treatment, Tbil level before treatment, IgG4/Tbil before treatment, and a combination of these indicators was high. Moreover, 15 (68.18%) patients with AIP had space-occupying lesions of the pancreas, and 16 (72.73%) had autoimmune cholangitis. Most patients with AIP were sensitive to hormone therapy. The Tbil and IgG4 levels, imaging findings, and hormone therapy reactivity could differentiate AIP from pancreatic cancer. A combination of IgG4, Tbil, and IgG4/Tbil before treatment might be a promising diagnostic biomarker for AIP.